Association of MTMR3 rs12537 at miR-181a Binding Site with Ischemic Stroke in Southern Chinese Han Population - Chen L; Wei S; Zhang Y; Li Y; Li Z; Huang P; Xiao C; Zhang Y (International Journal of General Medicine)
Linfa Chen,1,2,* Shan Wei,2,* Yutian Zhang,3,* You Li,3 Zishan Li,2 Pengru Huang,1 Chun Xiao,2 Yusheng Zhang1 1Department of Neurology, The First Affiliated Hospital of Jinan University, Guangzhou, 510630, People’s Republic of China; 2Huizhou Third People’s Hospital, Guangzhou Medical University, Huizhou, 516002, People’s Republic of China; 3Guangdong Key Laboratory of Age-Related Cardiac and Cerebral Diseases, Affiliated Hospital of Guangdong Medical University, Zhanjiang, 524001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yusheng Zhang, Department of Neurology, The First Affiliated Hospital of Jinan University, Guangzhou, 510630, People’s Republic of China, Email zhangys@jnu.edu.cn Chun Xiao, Huizhou Third People’s Hospital, Guangzhou Medical University, Huizhou, 516002, People’s Republic of China, Email HuizhouXiaoc@163.comBackground: Single nucleotide polymorphisms (SNPs) at microRNA (miRNA)--binding sites influence the development of ischemic stroke (IS) by affecting the expression of specific target genes. Myotubularin-related protein 3 (MTMR3), which is involved in autophagy, is directly targeted by miR-181a. This research examined the potential association between the SNP rs12537 in the miRNA-181a binding location within the 3′ untranslated region (3′-UTR) of MTMR3 and the incidence and prognosis of IS.Methods: An improved multitemperature ligase detection reaction assay was used to perform genotyping analysis in two independent case-control datasets consisting of 1128 subjects with IS and 1140 healthy controls with matched ages.Results: The distribution frequencies of the T allele (p = 5.2× 10− 4) of SNP rs12537 in MTMR3 were elevated significantly in IS patients as compared to healthy controls. Further categorization based on IS subtypes revealed that individuals carrying the variation T allele were linked with a higher risk of suffering large-artery (p = 1.2× 10− 3) and small-artery (p = 7.0× 10− 4) atherosclerotic stroke subtypes. The T allele of rs12537 was shown to be linked to both moderate and severe stroke (NIHSS ≥ 6) (p = 0.011), as well as a poor short-term outcome (p = 0.016) of IS. A significant correlation was also found between the rs12537 T allele mutation and a decrease in MTMR3 (p = 0.019), as well as an elevated miR-181a (p = 0.021) and LC3B (p = 0.026) in individuals with IS.Conclusion: This study identified a novel role for the rs12537 variant in influencing IS susceptibility and prognosis, potentially by modulating MTMR3 expression and leading to increased autophagy.Keywords: ischemic stroke, MTMR3, polymorphism, risk, prognosis